Biological puzzles solved by using Streptococcus pneumoniae : a historical review of the pneumococcal studies that have impacted medicine and shaped molecular bacteriology - Hiller, N. Luisa; Orihuela, Carlos J. (Journal of bacteriology, 2024)
The major human pathogen has been the subject of intensive clinical and basic scientific study for over 140 years. In multiple instances, these efforts have resulted in major breakthroughs in our understanding of basic biological principles as well as fundamental tenets of bacterial pathogenesis, immunology, vaccinology, and genetics. Discoveries made with have led to multiple major public health victories that have saved the lives of millions. Studies on continue today, where this bacterium is being used to dissect the impact of the host on disease processes, as a powerful cell biology model, and to better understand the consequence of human actions on commensal bacteria at the population level. Herein we review the major findings, i.e., puzzle pieces, made with and how, over the years, they have come together to shape our understanding of this bacterium's biology and the practice of medicine and modern molecular biology.